PENERAPAN MODEL PEMBELAJARAN KOOPERATIF JIGSAW DALAM MENINGKATAKAN HASIL BELAJAR LARI JARAK PENDEK SMPN 2 SEMARANG - Aditia , Dadang; Hartadi, Rinto (YLPK Mahardhika, 2025)
Engaging in regular physical exercise is one of the key strategies to promote better health. Well-organized and thoughtfully planned physical education programs can enhance intellectual abilities, foster skills development and boost physical fitness. One common form of physical activity involving the legs is short-distance running. This research focused on assessing the implementation of the jigsaw cooperative learning model to enhance short-distance running skills among students at SMP Negeri 2 Semarang. Conducted as Classroom Action Research (CAR), the study targeted Grade VII students, with a sample of 32 participants from Class VIIC. The results revealed a significant improvement in students' short-distance running abilities after using the jigsaw learning model. During the pretest, 19 students (59.50%) did not meet the minimum competency standard, while 13 students (40.62%) achieved it. In contrast, the posttest results showed that only 5 students (15.62%) failed to meet the standard, whereas 28 students (84.37%) successfully achieved or surpassed the required level.